2019
DOI: 10.1371/journal.pone.0217054
|View full text |Cite
|
Sign up to set email alerts
|

Effects of oregano essential oil on the ruminal pH and microbial population of sheep

Abstract: Oregano essential oil (OEO), which has antimicrobial properties, may be used for altering the ruminal pH and microbial populations of sheep, as observed by the altered volatile fatty acid patterns. To further elucidate the effects of OEO on ruminal pH and microbial populations of sheep, 3 German merino sheep × local sheep crossbred rams with permanent ruminal fistulas were randomly assigned to a 3 × 3 Latin square design with 12-d periods. The treatments were as follows: control (CON); OEO4: OEO supplied at 4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 52 publications
3
27
0
Order By: Relevance
“…Supplementation of oregano EO at 4 and 7 g/d promoted the population of primary cellulolytic bacteria and ruminal fungi, respectively, in sheep ( 241 ). An in vitro study revealed that the inclusion of EO of S. spicatum in a high-concentrate diet significantly improved the rumen fermentation characteristics by reducing CH 4 and NH 3 -N while promoting propionate concentration ( 252 ).…”
Section: Dietary Manipulation Of Rumen Function Using Natural Feed Admentioning
confidence: 99%
“…Supplementation of oregano EO at 4 and 7 g/d promoted the population of primary cellulolytic bacteria and ruminal fungi, respectively, in sheep ( 241 ). An in vitro study revealed that the inclusion of EO of S. spicatum in a high-concentrate diet significantly improved the rumen fermentation characteristics by reducing CH 4 and NH 3 -N while promoting propionate concentration ( 252 ).…”
Section: Dietary Manipulation Of Rumen Function Using Natural Feed Admentioning
confidence: 99%
“…Adding 1.25 g/kg DM of thyme essential oil improved both ruminal fermentation and nitrogen metabolism [ 48 ]. Another study investigating the effects of oregano essential oils on sheep showed an increase in the population of three primary cellulosic bacteria and ruminal fungi, affecting the rumen fermentation process [ 49 ]. However, potential toxic effects of plant essential oils are not scarce and should be taken into consideration before feeding them to animals [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…The main components of OEO and TEO are carvacrol, thymol, and α-terpene (5). Carvacrol is a non-toxic monoterpene, widely studied for its pharmacological properties such as antibacterial and antifungal activities (12).…”
Section: Discussionmentioning
confidence: 99%
“…Chlorhexidine (CLX) is also on the list of the most used chemical agents due to its antibacterial action against a wide range of aerobic and anaerobic bacteria (4). Besides, oregano essential oil (OEO) and thymus essential oil (TEO) have been associated with an important antimicrobial activity against Gram-positive and Gram-negative bacteria due to the presence of carvacrol, thymol, and α-terpene (5).…”
Section: Introductionmentioning
confidence: 99%